Relationship Between Environmental Permitting Laws and Economic Development from the Perspective of Maqashid al-Shariah - Achmad Muchsin (Prophetic Law Review)
Economic development is fundamentally aimed at fulfilling human needs. The ever-increasing human needs are inversely related to the environment's declining support and carrying capacity. This condition demands efforts to ensure that human needs are met while environmental sustainability is maintained. One legal instrument used to regulate the interaction between humans and the environment to fulfill human needs while preserving the environment is through environmental permitting laws. The essence of using the environmental permitting legal instrument to regulate the interaction between humans and the environment aligns with the basic principles of maqashid al-shariah, namely jalbul mashalih wa dar'u al mafasid (bringing benefits and avoiding harm/damage). This study seeks to answer the question, "How is the relationship between environmental permitting law and economic development from the perspective of maqashid al-shariah?" This is doctrinal legal research using legislative, conceptual, and philosophical approaches. Data collection was conducted using document studies, while data analysis was performed using qualitative data analysis techniques. The research findings indicate a relationship between environmental permitting law, economic development, and maqashid al-shariah. From the perspective of maqashid al-shariah, economic development aimed at fulfilling human needs and using environmental permitting legal instruments to regulate the interaction between humans and their environment is an implementation of jalbu al mashalih wa dar-u al mafasid.